The impact of spiritual and individual factors on social problems and mental health of Malaysian adolescents / Norfatmazura Che Wil and Nooraini Othman - Che Wil, Norfatmazura; Othman, Nooraini (Universiti Teknologi MARA, 2021)
The increase in social problems among adolescents from time to time proves that the level of mental health among adolescents is at an alarming level. Various factors need to be given serious attention to curb this issue from spreading. The study aims to explore spiritual factors and individual factors in adolescents as contributing factors and identify their impact on social and mental health problems. The study involved a total of 11 respondents consisting of adolescents who faced a bond of good behaviour. A qualitative study along with a purposive sampling method is used in this study. Findings show that spiritual factors involve factors of belief and motivation to worship while in terms of individuals involving personality formation, feelings of complex inferiority, as well as lack of social interest, have been identified. It is hoped that the recommendations and limitations through this study can be used as a reference and guide to the parties involved in formulating various aids and treatments to help adolescents from getting involved in social and mental health problems in the future.